Netherton syndrome in two sisters. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Netherton syndrome is an autosomal recessive disorder, due to a mutation of gene SPINK5, mapped to 5q32 (2). It is characterized by trichorrhexis invaginata, atopy and skin lesions ranging from circinate, erythematous and scaling to ich-thyosiform erythroderma. The gene defect could be responsible for a disorder of the keratinization, with altered skin barrier and brittle hair. The severity of the syndrome, which is greater in males (4), is related to the type of skin lesions. In the severest cases there are really persistent, ichthyosiform lesions, whereas in the mild cases there are erythematous and scaling, circinate lesions, reminiscent of pityriasis rosea. Hypernatremia, hypothermia, seizures, growth deficiency, specially in the first months of age (3) characterize the severest cases. In the latter there can be systemic immune suppression due to absorption of topical drugs such as tacrolimus (1). However, Netherton syndrome has a tendency to improve with time.